2020
DOI: 10.36351/pjo.v36i1.897
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of epiretinal membrane peel after dual staining versus en bloc peel using negative staining technique

Abstract: Purpose:  To compare the completeness of ILM peel in cases of Idiopathic Epiretinal Membranes following double staining and double peeling  versus en bloc dissection of both using negative staining method. Study Design:  Quasi experimental study. Place and Duration of Study:  Jinnah Hospital Lahore, from October 2017 to March 2018. Material and Methods:  Forty eyes of forty patients with Idiopathic Epiretinal membranes (ERM) were selected by non-probability convenient method and divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…documented that a large number of such injuries could be well prevented by use of such protective measures including glasses, helmets and eye shields etc. 20 The main limitation of this study is single center study with a small sample size. We recommend a multicentric study with larger sample size.…”
Section: Discussionmentioning
confidence: 93%
“…documented that a large number of such injuries could be well prevented by use of such protective measures including glasses, helmets and eye shields etc. 20 The main limitation of this study is single center study with a small sample size. We recommend a multicentric study with larger sample size.…”
Section: Discussionmentioning
confidence: 93%
“…The mean time from injury to patient admission was 6 h. The majority of the cases (95%) presented to the hospital within 24 h, which is slightly higher than the studies conducted in Nigeria, Egypt, and Pakistan. [ 18 20 ] In most cases, the time between admission to hospital and surgery was at most 6 h, which may be due to the affordability of rapid response to eye injuries in the two major cities in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Even relatively minor eye injuries can result in discomfort, missed work, and medical costs. Identifying preventive measures requires determining the causes and extent of ocular trauma [12]. Iftikhar et al [13] reported an incidence of primary eye trauma of 3.0 per 100 000 individuals, and the lifetime prevalence is 13.5% for men in the USA [14].…”
Section: Introductionmentioning
confidence: 99%